Epidemiological Overview of Drug-Resistant Tuberculosis (DR-TB) Cases In Kendari City, 2021–2025: A Case Series Study - Listy Handayani (Journal of Epidemiology and Health Science, 2026)
Background: Drug-Resistant Tuberculosis (DR-TB) is one of the major challenges in tuberculosis control efforts in Indonesia, given the increasing transmission of resistant strains and the low treatment success rate. Indonesia is one of the five countries that contribute to 50% of all MDR-TB cases worldwide and ranks third after India and the Russian Federation, with a prevalence of 7.4% and a treatment success rate for new DR-TB cases of only 58%. Objectives: This study aims to provide an epidemiological overview of DR-TB cases in Kendari City for the period 2021–2025. Methods: A quantitative descriptive was employed in this study with a case series design. This study used secondary data from the Tuberculosis Information System (SITB) of the Kendari City Health Office. A total of 174 DR-TB cases recorded during the period of 2021 to May 2025. Data were analyzed using univariate methods and presented in frequency distribution tables and graphs to describe demographic characteristics, geographic distribution, treatment history, and comorbidities of DR-TB cases. Results: The result showed that DR-TB cases are predominantly found in the productive age group of 30–59 years (56%) and occur more frequently in males (66%). Based on geographic distribution, 37% of patients were from Kendari City, resistance patterns were dominated by new cases (36%) and relapse cases (35%). The most common comorbidity was Diabetes Mellitus (13%), while HIV/AIDS was identified in only a small proportion of cases (2%). Conclusion: These findings underscore that DR-TB in Kendari City is influenced by community transmission dynamics, treatment adherence, and underlying health conditions. Strengthening early detection, comorbidity screening, treatment support, and community education is needed to reduce transmission rates and improve treatment outcomes for DR-TB in this area. Keywords: comorbidities; drug-resistant tuberculosis, epidemiology, geographic distribution, treatment history